Integrasi Arificial Intelegent dalam Pendidikan Islam: Tantangan dan Peluang - Miftakhul Munir; Umu Nur Lathifah; Afina Na’imatul Kamalia; Siti Ulfia Madani; Anisa Latifatul Khoeriyah (Kartika: Jurnal Studi Keislaman, 2024)
The rapid development of Artificial Intelligence (AI) has significantly transformed various sectors, including education. However, its integration into Islamic education raises academic concerns regarding epistemological compatibility, ethical considerations, and the preservation of spiritual values. This study aims to analyze the opportunities and challenges of integrating AI within the framework of Islamic education. The research employs a library research method by examining relevant scholarly books, journal articles, and academic publications related to AI and Islamic educational philosophy. The findings indicate that AI offers strategic opportunities such as personalized learning, efficiency in assessment, adaptive instructional systems, and transformation of teachers’ roles into spiritual and intellectual facilitators. Nevertheless, the integration of AI also presents multidimensional challenges, including ethical risks, potential dehumanization of learning processes, digital inequality, and the need for clear regulatory frameworks. Therefore, the successful implementation of AI in Islamic education requires a balanced approach that aligns technological innovation with Islamic moral and spiritual principles. AI should function as a supportive instrument rather than replacing the essential human relationship between teachers and students